Motivations, learning and creativity in online citizen science - Jennett, Charlene; Kloetzer, Laure; Schneider, Daniel; Iacovides, Ioanna; Cox, Anna; Gold, Margaret; Fuchs, Brian; Eveleigh, Alexandra; Methieu, Kathleen; Ajani, Zoya; Talsi, Yasmin (My University, 2016)
Online citizen science projects have demonstrated their usefulness for research, however little is known about the potential benefits for volunteers. We conducted 39 interviews (28 volunteers, 11 researchers) to gain a greater understanding of volunteers’ motivations, learning and creativity (MLC). In our MLC model we explain that participating and progressing in a project community provides volunteers with many indirect opportunities for learning and creativity. The more aspects that volunteers are involved in, the more likely they are to sustain their participation in the project. These results have implications for the design and management of online citizen science projects. It is important to provide users with tools to communicate in order to supporting social learning, community building and sharing.
Keywords: Citizen science; Informal learning; Public engagement with science and technology.